TRANSFORMATION OF CULTURAL VALUES IN FORMING CHARACTER BASED ON LOCAL WISDOM - Suidat Suidat; Andjela Lenora Kelmaskouw; Ahmad Deing; Bonin Bonin; Bambang Agus Haryanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
In essence, culture has values that are always inherited, interpreted, and implemented along with the process of social change. The implementation of cultural values is a manifestation and legitimacy of society towards culture. The existence of culture and the diversity of noble cultural values possessed by the Indonesian nation is a means of building the character of citizens, both related to private character and public character. Every cultural diversity of ethnic groups in Indonesia has local advantages or has different local wisdom. This local wisdom is reflected in the living habits of the local community that have lasted a long time. This study uses a qualitative approach. The researcher chose this approach because he wanted to know directly and deeply about the process of transforming local wisdom values as an effort to build national character. From this research it is hoped that as much data as possible can be collected about the transformation of local wisdom values as an effort to build national character without compromising the accuracy of the data obtained. The results of the study show that the development of national character needs to be carried out outside of school or in society in general according to the wisdom of each local culture. Preservation of regional culture and development of national culture through education, both formal and non-formal, by reactivating all educational platforms and activities. One of the means to build national character is by transforming local wisdom values